COMMERCIAL BEHAVIOUR OF SMALLHOLDER POTATO PRODUCERS: THE CASE OF KOMBOLCHAWOREDA, EASTERN PART OF ETHIOPIA - Alamerie, Kumilachew (Economics of Agriculture, 2016)
Meeting the challenge of improving rural incomes in Ethiopia will require some form of transformation of the subsistence, low-input and low-productivity farming systems to agricultural commercialization. In the process, commercial production of high value food crops like potato would have been expected. Nonetheless, in the study area, Kombolcha Woreda, the extent to which farmers have commercialized potato production was not known. This study was then undertaken to analyse the extent to which potato was oriented towards the market (denoted by commercialization index) and identify the factors affecting commercialization of potato. A multi-stage sampling technique was used to select 130 sample households from six sample kebeles. In the study, both primary and secondary data sources were used. Results showed that potato production was lucrative and semi-commercialized i.e. about 59.50% of the potato produce were sold. Moreover, the two limit-Tobit regression model results indicated that non/off farm income, access to information, access to improved seed and access to irrigation affect proportion of the value of potato sold positively and signifcantly while number of plots affects it negatively. Hence, policies should emphasis on reducing land fragmentation, creating awareness on non/off farm employment, and offer improved seeds and irrigation facilities to farmers and access information.